Hymenobacter polaris sp. nov., a psychrotolerant bacterium isolated from an Arctic station - Dahal, Ram Hari; Chaudhary, Dhiraj Kumar; Kim, Dong-Uk; Kim, Jaisoo (International journal of systematic and evolutionary microbiology, 2020)
A pink-pigmented, non-motile, Gram-stain-negative, rod-shaped bacterium, designated RP-2-7 T , was obtained from soil sampled at the Arctic station, Spitsbergen, Svalbard, Norway. Cells were strictly aerobic, psychrotolerant, grew optimally at 15–20 °C and hydrolysed CM-cellulose. Phylogenetic analysis based on its 16S rRNA gene sequence revealed that strain RP-2-7 T formed a lineage within the family Hymenobacteraceae and clustered with members of the genus Hymenobacter . Its closest relative was Hymenobacter marinus KJ035 T (97.6 % sequence similarity). The sequence similarities to other strains were ≤96.9 %. The principal respiratory quinone was MK-7 and the major polar lipids were phosphatidylethanolamine and an unidentified aminophospholipid. The predominant cellular fatty acids were summed feature 3 (C 16 : 1 ω 7 c and/or C 16 : 1 ω 6 c ), anteiso-C 15 : 0 , iso-C 15 : 0 , C 16 : 1 ω 5 c and summed featured 4 (iso-C 17 : 1 I and/or anteiso-C 17 : 1 B). The DNA G+C content was 62.8 mol%. In addition, the average nucleotide identity and in silico DNA–DNA hybridization relatedness values between strain RP-2-7 T and closely related strains were lower than species demarcation thresholds. Based on the resuls of genomic, chemotaxonomic, phenotypic and phylogenetic analyses, strain RP-2-7 T represents novel species in the genus Hymenobacter , for which the name Hymenobacter polaris sp. nov. is proposed. The type strain is RP-2-7 T (=KACC 21670 T =NBRC 114391 T ).